Communication in Physiotherapy Programme Development in Medical Rehabilitation - Wiranti, Mira; Wasliati, Balqis; Br Bangun, Sri Melda (Public Health and Safety International Journal, 2024)
Despite the recognition of the importance of physiotherapy, the implementation of physiotherapy programmes in Medical Rehabilitation Centres in many hospitals still faces various obstacles. Some hospitals do not fully understand the benefits of physiotherapy or do not have sufficient resources to develop the programme. This is in accordance with the theory of policy implementation from George C. Edward III's theory of policy implementation including communication, resources, disposition, and bureaucratic structure. Methods This study is a descriptive qualitative research. The research was conducted at the Medical Rehabilitation Centre of Sultan Iskandar Muda Nagan Raya Hospital. The research informants were 6 people, the sample was taken by snowballing. Data were analysed in depth in narrative form by reducing data, presenting data, drawing conclusions / verification. The study showed that the physiotherapy programme at the Medical Rehabilitation Centre of RS Sultan Iskandar Muda uses regular meetings, in-person meetings, and online groups for communication. Patients get initial information from doctors and detailed explanations from physiotherapists, which builds trust. The implementation of the physiotherapy programme development policy is effective thanks to good communication. It is recommended to improve physical facilities and physiotherapy equipment and increase physiotherapy personnel through recruitment of new ASNs to ensure optimal service for patients.